Agonist redirected checkpoint, PD1-Fc-OX40L, for cancer immunotherapy. Issue 1 (18th December 2018) - Fromm, George; de Silva, Suresh; Johannes, Kellsey; Patel, Arpita; Hornblower, Josiah C.; Schreiber, Taylor H.
Abstract : Simultaneous blockade of immune checkpoint molecules and co-stimulation of the TNF receptor superfamily (TNFRSF) is predicted to improve overall survival in human cancer. TNFRSF co-stimulation depends upon coordinated antigen recognition through the T cell receptor followed by homotrimerization of the TNFRSF, and is most effective when these functions occur simultaneously. To address this mechanism, we developed a two-sided human fusion protein incorporating the extracellular domains (ECD) of PD-1 and OX40L, adjoined by a central Fc domain, termed PD1-Fc-OX40L. The PD-1 end of the fusion protein binds PD-L1 and PD-L2 with affinities of 2.08 and 1.76 nM, respectively, and the OX40L end binds OX40 with an affinity of 246 pM. High binding affinity on both sides of the construct translated to potent stimulation of OX40 signaling and PD1:PD-L1/L2 blockade, in multiple in vitro assays, including improved potency as compared to pembrolizumab, nivolumab, tavolixizumab and combinations of those antibodies. Furthermore, when activated human T cells were co-cultured with PD-L1 positive human tumor cells, PD1-Fc-OX40L was observed to concentrate to the immune synapse, which enhanced proliferation of T cells and production of IL-2, IFNγ and TNFα, and led to efficient killing of tumor cells. The therapeutic activity of PD1-Fc-OX40L in established murine tumors was significantly superior to either PD1 blocking, OX40 agonist, or combination antibody therapy; and required CD4+ T cells for maximum response. Importantly, all agonist functions of PD1-Fc-OX40L are independent of Fc receptor cross-linking. Collectively, these data demonstrate a highly potent fusion protein that is part of a platform, capable of providing checkpoint blockade and TNFRSF costimulation in a single molecule, which uniquely localizes TNFRSF costimulation to checkpoint ligand positive tumor cells.